Investigation of Preliminary Student Test Performance Data Using the ANOM Statistical Tool and Mixed Model Analysis - Bazdan, Vanda
The goal of this paper is to demonstrate the analytical use of a statistical tool ANOM (more commonly used by quality control engineers), mixed model analysis and other statistical tools (used in social sciences) to investigate differences found in Croatian high school student performance in mathematics examinations, recently developed as part of the National Assessment project.